Hybrid Nasal Filler: Combining Agarose Gel and Hyaluronic Acid for Nonsurgical Rhinoplasty - KİRAZOĞLU, AHMET; Buhsem, Omer; KİRAZOĞLU, AHMET (My University, 2022)
Introduction: Given its structural properties, it would be a mistake to assume that a single type of filler fits perfectly to each anatomical region of the nose in nonsurgical rhinoplasty procedures. Therefore, we aimed to develop a hybrid treatment model by applying two different structural types of fillers. Hyaluronic acid (HA), a hydrophilic material, and agarose gel (AG), a nonhydrophilic and high G-prime material, were used in the study according to their advantages and disadvantages. Methods: Patients who presented to the office desiring filler treatment for nonsurgical correction of the nose in a 2-year period were enrolled in the study. HA was used intradermally 0.1ml per each point in the tip defining points and supratip. Injections of 0.4–0.7 and 0.4–0.6ml AG were used supraperiosteally in the radix and nasal spine, respectively. Clinical improvement was evaluated two weeks later using the Global Aesthetic Improvement Scale from 1 to 5 (1: exceptional improvement; 5: worsened patient). Patient satisfaction was evaluated on a scale from 0 to 10 (0: not satisfied; 10: very satisfied). Results: A total of 32 patients (mean age: 27 years) were enrolled in the study. Mean score of patient satisfaction was 9.09 of 10 after injection and 9 of 10 after 2 weeks. Clinical evaluation scores after injection were 1.72 of 5 and 1.69 of 5 on the Global Aesthetic Improvement Scale. No major complication was observed. Conclusion: The HA and AG filler hybrid concept applied in different anatomical locations represents a safe and convenient option for nonsurgical rhinoplasty procedures.
Keywords: Nonsurgical Rhinoplasty